Tips and Pitfalls in Using Social Media Platforms for Survey Dissemination - William Lay Keat Ong; Vineet Gauhar; Daniele Castellani; Jeremy Y.C. Teoh (Société Internationale d’Urologie Journal)
IntroductionSocial media has become a prevalent platform for survey dissemination, despite the paucity of literature on this topic. The purpose of this paper is to outline the benefits and drawbacks of and best practices for social media-based surveys.MethodsWe performed a scoping review of this topic and explored different strategies commonly employed for conducting efficient health care surveys via social media platforms.ResultsThe main advantages of social media-based surveys are the convenience and flexibility of survey design, their relatively low cost, the anonymity of responders, and the ability to reach a broader population of responders across geographical boundaries. Several measures can be adopted to avoid issues inherent in this approach, such as data disruption and response duplication, as well as to enhance ethical behaviors and consent compliance. We discuss limitations associated with unclear distribution of survey respondents and outline survey fraud as a major impediment to the online propagation of surveys on various social media platforms.DiscussionThe use of social media to disseminate surveys on various medical specialty topics has garnered global participation, particularly during the COVID-19 pandemic. Ethical codes of conduct emphasize the need for professionalism and truthfulness, and disclosure of potential conflicts of interest on the part of respondents, and high-quality survey research on the part of researchers.ConclusionWe advocate for the novel use of social media to promote large and diverse health care surveys. Additional studies should further explore the use of emerging social media platforms for survey dissemination and their impact on health care research.